Banishing bullying behavior : transforming the culture of pain, rage, and revenge - Fried, SuEllen (Rowman & Littlefield Education, 2009)
Fried and Sosland bring their combined experiences together to present a blueprint to reduce the pain, rage and revenge cycle of bullying. Their strategies have been captured from hands-on interaction with educators, parents and students. Their premise comes from the apocryphal village that is being ravaged by dysentery. Do you treat each person for their intestinal disorders or do you put in a sewer system? Do you work with each individual student or do you change a culture that hosts cruelty. Can you doboth? The core of the book is the Student Empowerment Session that has been crafted and refined over fifteen years. This carefully organized, powerful system of questions has effected dramatic changes in children's insights about their behavior. The book also explores topics which include cyberbullying, children with disabilities, "mean girls," teachers who are bullies, parents who refuse to accept that their children are bullies, and academic vs. social emotional learning concerns to help readers change the culture and banish bully behavior